PENGARUH PAJANAN PARTIKEL KARBOFURAN TERHADAP KELUHAN SUBJEKTIF PEKERJA DI BAGIAN PRODUKSI PT PETROKIMIA KAYAKU GRESIK - Devisnaini Rahmah; Rachmaniyah .; Sri Mardoyo (Poltekkes Kemenkes Surabaya, 2015)
PT Petrokimia Kayaku Gresik is a company engaged in the field of pesticides. Its productionprocess is divided into several parts: liquid, powder (granules), solids and biological fertilizersproduction. The production process includes process of making Petrofur products that usecarbofuran raw material that cause dust resulting direct exposure to workers in production section.Identification toward characteristics of production worker showed that some workers did not wearpersonal protective equipment such as masks and gloves, therefore subjective complaints andhealth problems appeared. Research was conducted analytically with cross sectional approach. Dust was measured by usingHVDS and questionnaire to 30 people. This study used statistical test of